Impact of networking on career progression: Moderating role of gender - Saiqa Saddiqa Qureshi; Farida Saleem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The purpose of the study was to investigate the moderating role of gender in the relationship of networking behavior's and career progression of individuals. Five dimensions of networking behavior's: Maintaining Contacts (MC), participating in Community (PC) increase in Internal Visibility (IIV), engaging in Profession Activities (EPA), and socializing (NS) were taken in consideration. A structured questionnaire was used to collect data from 29 banks (head offices and more than 100 branches) from major cities of Pakistan. The proposed model was tested using a sample of 332. Structural Equation Modelling technique and group difference test was used for data analysis. Results indicated that EPA and PC relationships of networking behaviors were not moderated while MC, IIV and NS are moderated by gender. MC and IIV have stronger relationship with career progression of males. However, NS has stronger relationship with career progression for females. Despite glass ceiling prevalent in Pakistan, these findings suggest that socializing plays a significant role in the career progression of females. Despite the limitations including common method variance and generalizability issue the current study's findings can be help in developing strategies for career progression of males and females in Pakistan.
Keywords: 330; Structural equation modelling; networking behaviors; career progress; Pakistan; gender